The Woman Who Knew How to Govern Bolivar’s Ungovernable Country. A Saint-Simonian Reading of Francisca Zubiaga in Peregrinations of a Pariah - Denegri, Francesca (2025)
This article examines Flora Tristan's portrait of a female leader who gained notoriety for her open exercise of political power in the early Peruvian Republic. It argues that the feminist discourses that emerged during the revolutions of 1789, 1830 and 1848 in France, in particular Saint-Simonian feminism, along with the patriotic gender debate in Peru, constitute the central threads of this complex, foundational travel narrative. When the literary subject comes into contact with historical Peruvian female characters foreign to French imaginaries, her place of enunciation is destabilized and her visionary force is enhanced and magnified. In the process of constructing Zubiaga as a public figure, Tristan discovers a narrative space in which she can negotiate her own identity in the face of intensely antagonistic gender mandates; this reckoning will enable her reinvention as the leader of a new emancipatory politics of class and gender.